Miskonsepsi Pengerjaan Operasi Deret Aritmatika di PGMI-3 UIN Sumatera Utara - Khoiriah Marta Parapat; Rora Rizki Wandini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Misconceptions are misunderstandings or inequalities in solving mathematics learning problems by understanding concepts that are in accordance with mathematical rules or scientists' concepts. This journal aims to find out misconceptions about teaching arithmetic series that occur among students based on misconception indicators. The method used in this writing is qualitative-descriptive. There were 18 research subjects carried out at PGMI 3 UIN North Sumatra. There are often or still are some students who experience misconceptions about arithmetic series material, both from conceptual, strategic and systematic misconceptions, but in translation there are no more misconceptions. The data collection techniques used were observation and questionnaire questions. The results of the analysis that has been carried out are that in the process of learning arithmetic series, there are still some misconceptions among students due to a lack of understanding of the concept and not being careful in determining strategies for arithmetic series material, resulting in errors in solving problems.